Enhancing antibiotic detection via an aptasensor: the case of ciprofloxacin - Eva Hobeika; Joseph Saab; Souheil Hallit; Isaac-Aaron Morales Frias; Nicole Jaffrezic-Renault; Abdelhamid Errachid (BMC Chemistry)
Abstract The need for fast, efficient, and cost-effective test systems for antibiotics is surging, to control resistant bacterial strains. Electrochemical biosensors offer a good alternative to routine laboratory-bound analytical methods. These biosensors are portable, suitable for in-field analysis and biocompatible for detection of small biomolecules. The aim of this work is the ciprofloxacin active pharmaceutical ingredient since resistance of bacteria to this antibiotic is reportedly increasing worldwide, especially in Lebanon where hospitalization bills are no longer affordable. So, the target is ciprofloxacin detection, a fluoroquinolone antibiotic, on screen-printed electrodes. Following diazonium salt, also known as carboxymethylaniline (CMA) deposition, a ciprofloxacin oligonucleotide was incubated on the electrode. This aptamer acts as an anchor for the ciprofloxacin molecule, allowing the latter’s attachment to the electrode and its quantification. Electrochemical characterization, through cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) allowed for deposition of molecules on electrodes and confirmation that an electrochemical change took place. Scanning Electron Microscope images are used to confirm conformational changes on the surface of electrodes. Impedance results reported a limit of detection of LOD = 3 nM, a dynamic range from 10 nM to 100 µM, and reproducibility of results between two aptasensors to be 10%. Moreover, impedimetric sensor specificity evaluation was through the effect of interfering compounds tobramycin, ofloxacin, norfloxacin and ceftriaxone, on the aptasensor’s response. Based on available literature, this LOD level reached allows for the detection of ciprofloxacin via a portable potentiostat in environmental (wastewater, food), biological (urine, saliva) and pharmaceutical samples (efficient market withdrawal of counterfeit medications from pharmaceutical storage facilities).